2021
DOI: 10.3389/fphy.2021.678600
|View full text |Cite
|
Sign up to set email alerts
|

Larval Zebrafish Exhibit Collective Circulation in Confined Spaces

Abstract: Collective behavior may be elicited or can spontaneously emerge by a combination of interactions with the physical environment and conspecifics moving within that environment. To investigate the relative contributions of these factors in a small millimeter-scale swimming organism, we observed larval zebrafish, interacting at varying densities under circular confinement. If left undisturbed, larval zebrafish swim intermittently in a burst and coast manner and are socially independent at this developmental stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…For the source in Fig. 3(b) the horizontal velocity u x displays an increasing maximum as the observation point x approaches the singularity location, while the vertical velocity component u z has a positive divergence for z → h + and a negative divergence as z → h − as expected for a source, while vanishing at the top and bottom boundaries, as required by (11). Both the rotlet dipole in Fig.…”
Section: Auxiliary Solutionmentioning
confidence: 73%
See 1 more Smart Citation
“…For the source in Fig. 3(b) the horizontal velocity u x displays an increasing maximum as the observation point x approaches the singularity location, while the vertical velocity component u z has a positive divergence for z → h + and a negative divergence as z → h − as expected for a source, while vanishing at the top and bottom boundaries, as required by (11). Both the rotlet dipole in Fig.…”
Section: Auxiliary Solutionmentioning
confidence: 73%
“…when studying Liesegang rings [3,4]) or in entomology where they are convenient enclosures to study the behaviour of insects and small animals [5,6]. A Petri dish environment is also a simple and common setting in which to examine the locomotion of swimming organisms, particularly those whose body size is tens of microns to millimetres [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Using this setup, we examined behavioral impacts of the size of behavioral arenas by comparing swimming trajectories between those in a small, walled arena (30 mm) and those in a large unwalled arena (90 mm). Zebrafish typically swam near the wall in the small arena due to their innate preferences called thigmotaxis 51 . In our large arena, on the contrary, they explored widely (Figures 1B and 1C) and swam longer distances during visual stimulus motion (Figure 1D).…”
Section: Resultsmentioning
confidence: 99%
“…As described in Section "Other Defensive Behaviors" and "Social Feeding Behavior, " the presence or absence of conspecifics influences feeding and defensive behavior . Circling behavior -defined as multiple conspecifics moving in an organized manner along the edges of the arena towards one direction -was observed in dishes with dense zebrafish populations and occurred more frequently along with increased densities (Zaki et al, 2021). Furthermore, it was also shown that larvae in dense arenas preferred edges and the outer circumferences of the arena.…”
Section: Referencesmentioning
confidence: 97%
“…Age Learned helplessness, locomotion, light/dark choice and transition, social aggregation/preference/orienting Lee et al, 2010;Lau et al, 2011;Padilla et al, 2011;Valente et al, 2012;Dreosti et al, 2015;Andalman et al, 2019;Stednitz and Washbourne, 2020 Arena size and depth Locomotion Padilla et al, 2011;Ingebretson and Masino, 2013;Christou et al, 2020 Genotype/strain Light-dark transition, startle habituation, stress-induced anorexia O' Malley et al, 2004;van den Bos et al, 2017;Cheng et al, 2022 Feeding state and diet Locomotion, social preference/orienting, thigmotaxis, feeding Clift et al, 2014;Filosa et al, 2016, Wee et al, 2019bStednitz and Washbourne, 2020 Environmental state Feeding, locomotion, light/dark choice, sleep, startle habituation McHenry et al, 2009;Clark et al, 2011;Olszewski et al, 2012;Suli et al, 2012;Yeh et al, 2013;De Marco et al, 2014Bai et al, 2016;Olive et al, 2016;Oteiza et al, 2017;Bhandiwad et al, 2018;Cheng et al, 2022 Crowding/fish density Thigmotaxis, locomotion, social aggregation/avoidance, feeding, defensive behavior, startle responsiveness Burgess and Granato, 2008;Zellner et al, 2011;Delomas and Dabrowski, 2019;Groneberg et al, 2020;Zaki et al, 2021; Time of day Locomotion and arousal, startle responsiveness Zhdanova et al, 2001;…”
Section: Referencesmentioning
confidence: 99%